Answer:
![(2)/(39)](https://img.qammunity.org/2019/formulas/mathematics/college/h0kuy00tf0yy8vyx8myibwf7z1vwks3gil.png)
Explanation:
Given : A mini bag of Skittles has 3 lemon, 4 grape, 4 orange and 2 lime Skittles.
Total Skittles = 3+4+4+2=13
Probability of pulling an orange Skittle out first : P(First orange)
![=\frac{\text{No. of orange skittles}}{\text{Total skittles}}](https://img.qammunity.org/2019/formulas/mathematics/college/b7prodnoxxrcrklnkvh6e5fzcdfvlmhv3n.png)
![=(4)/(13)](https://img.qammunity.org/2019/formulas/mathematics/college/5sf31y7rreekricp5epxorouf8szmqbord.png)
Since the second skittles is drawn without replacement , so after drawing one skittle , the remaining skittles = 13-1=12
So , P(Second skittle is lime) =
![\frac{\text{No. of lime Skittles}}{\text{remaining skittles }}](https://img.qammunity.org/2019/formulas/mathematics/college/mr89twjpjfq0vqcgh5yoqtiy3j058vyhx0.png)
Since the events of pulling any Skittle are independent .
So , P( Orange then lime)= P(First orange) x P(Second skittle is lime)
![=(4)/(13)*(1)/(6)=(2)/(39)](https://img.qammunity.org/2019/formulas/mathematics/college/e2kmr9j9nif03wp8iouh4i9yp9vz2rquae.png)
∴ The probability of randomly pulling an orange Skittle out first and eating it and then pulling a lime Skittle out of the bag next =
![(2)/(39)](https://img.qammunity.org/2019/formulas/mathematics/college/h0kuy00tf0yy8vyx8myibwf7z1vwks3gil.png)